An investigation of the adoption of mobile money transfer service in Somaliland - Ahmed, Sa'ad Abdirisak (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2015)
The production of handheld devices and the high-speed mobile network have created another revolution in the world of commerce. Especially mobile commerce which is thought to be the next phase in technologically dependent society. Mobile Money Transfer Service is a type of mobile commerce which is mainly developed by Network Providers and Banks. This new service which is a new payment solution has emerged as part of mobile commerce. Thus, this study aims at examining the factors influencing customers' adoption of Mobile Money Transfer Services in Somaliland. Technology Acceptance Model (TAM) with two extra constructs were used to form the theoretical framework of the study. Therefore, the model comprises of four independent variables; Perceived Ease of Use, Perceived usefulness, Perceived Trust and Perceived Risk, and one dependent variable; Behavioral Intention to use and adopt the Mobile Money Transfer Service in Somaliland. The population of the research comprised of Somaliland citizens who reside in the country and use the service. The study used simple random sampling technique to select the participants. Out of 384 questionnaire that were distributed, 201 valid responses were received. Apparently, the research involved Telesom Telecommunication company customers who use Mobile Money Transfer services in Somaliland which is known as Zaad Service. In analysing the data collected, various statistical methods and techniques were used. Such tools are; the use of descriptive analysis in analysing respondents profile, multiple regression analysis for measuring relationships between variables, T-test for testing the influence of gender on relationships and ANOVA for testing the influence of different age groups on relationships. The results show that Perceived Ease of Use, Perceived Usefulness and Perceived Trust has positive significant influence on Behavioral Intention of customer's use and adoption the service while Perceived Risk did not have any significant influence. The extended model explained 75 percent of consumer's intention to use and adopt Mobile Money Transfer Service. In addition, the result show that there are no significant difference by gender on the influention to use the zaad service, but there are significant difference across different age groups.